In praise of a green stimulus. (6th November 2013) - Zenghelis, Dimitri
Abstract : Macroeconomic conditions make this a relatively favorable time to kick‐start investments necessary to transition to a resource‐efficient economy. There is no lack of private money, just a perceived lack of opportunity. Resource costs are low and the potential to crowd out alternative investment and employment is greatly reduced. It is often argued that the short‐term macroeconomic merit of an investment, in terms of what constitutes a good economic stimulus, can be judged against established criteria. These include tests on whether an investment is timely, temporary, and targeted. Although these are important, the evidence presented here suggests that a more important criterion for a sustainable economic impact is the ability to generate private sector confidence in profitable and enduring new markets. The world is likely to transition to a resource‐efficient, low‐carbon economy over this century and managing this transition has early pay‐offs. Clear and credible green policies have the potential restore confidence and generate growth. Providing credible early incentives to invest in resource‐efficiency could generate investment and growth in the long and the short run. WIREs Clim Change 2014, 5:7–14. doi: 10.1002/wcc.256 This article is categorized under: Climate Economics > Economics of Mitigation